MMSE filter design for Full-Duplex filter-and-forward MIMO relays under limited dynamic range - Emilio Antonio-Rodríguez; Stefan Werner; R. López-Valcarce; Risto Wichman (Signal Processing, 2019)
We study the problem of optimizing the end-to-end performance of a full-duplex filter-and-forward MIMO relay link, consisting of a source, a relay, and a destination node, by employing linear filtering at each node. The system model accounts for multipath propagation and self-interference at the relay, as well as transmitter impairments and limited dynamic range at every node. The design accommodates signals with arbitrary spectra and includes the direct link between the source and destination nodes. Under the minimum mean square error criterion, the resulting non-convex problem is approximated by a sequence of convex problems and solved by means of an alternating minimization method. Linear constraints allocate some of the degrees of freedom in the relay to guarantee a sufficiently small residual self-interference. Simulations quantify the impact of degrees of freedom, the dynamic range, and the balance between direct and relay paths on the link performance.
Keywords: adaptive signal processing; full-duplex; winter